Fabrication of an immobilized cross-linked chitosan-glyoxal film as an effective adsorbent for adsorption and desorption of reactive orange 16 and methyl orange dyes / Siti Solehah Ahmad Norrahma - Ahmad Norrahma, Siti Solehah (2020)
Chitosan was cross-linked with Glyoxal to produce an immobilized film of cross-linked chitosan-glyoxal film (Chi-Gly film) to act as potential adsorbent for Reactive Red 16 (RO16) and Methyl Orange (MO) dyes from aqueous solutions. The physicochemical properties of Chi-Gly film were determined via pH-Potentiometric titration, surface area (BET) analysis, elemental analysis, Scanning Electron Microscopy with Energy Dispersive X-Ray (SEM-EDX), X-Ray Diffraction (XRD), Thermogravimetric analysis (TGA), Fourier Transform Infrared Spectroscopy (FT-IR), pH at the point of zero charge (pHpzc), water swelling, and mechanical strength. The characterizations indicated that the Chi-Gly film was thermally stable, extremely low swelling index with high adhesion strength on glass plate, amine group (-NH2) content was 32.52 %, and pHpzc of ∼6.0 indicating a negative surface charge occurs above pHpzc. The maximum adsorption capacities for RO16 and MO on Chi-Gly film were 1554.3 mg/g and 1451.9 mg/g, respectively, at Chi-Gly film thickness of 8.5 μm, pH ~ 3, and temperature 303 K. The Langmuir isotherm model showed better fit to the equilibrium data than the Freundlich and Temkin models. The kinetic uptake results were well described by the Pseudo-First-Order (PFO) kinetic. The mechanism of adsorption included mainly hydrogen bonding interaction, electrostatic attractions, n-π stacking interaction and Yoshida H-bonding. The thermodynamic adsorption functions (ΔG°, ΔH° and ΔS°) showed that the adsorption of RO16 and MO on Chi-Gly film was spontaneous and exothermic in nature under examined conditions. This study revealed that immobilized Chi-Gly film as a potential and reusable adsorbent for at least three cycles of adsorptions without losing much its adsorptive activity and no filtration process was required for adsorbent recovery.